MENGATASI LEARNING OBSTACLE KONSEP TRANSFORMASI GEOMETRI DENGAN DIDACTICAL DESIGN RESEARCH - Ramdani Miftah; Lia Kurniawati; Ticha Putri Solicha (ALGORITMA: Journal of Mathematics Education, 2019)
The purpose of this study was to identify learning obstacle precisely on students' epistemological barriers to the concept of geometry transformation. Furthermore, researchers overcome these obstacles by developing mathematical learning concepts in the concept of geometry transformation in high school. This research was conducted at one of the senior high school in Tangerang Selatan. The research method used is Didactical Design Research. This method is carried out in three stages, the analysis of didactic situations before learning (prospective analysis), metapedidactic analysis, and retrospective analysis. Based on the results of the preliminary study, of the 20 students who took the obstacle learningidentificationtest,82.35%ofthetotalstudentsexperiencedepistemologicalbarrierstotheconceptofgeometry transformation. In overcoming the epistemological obstacles students in the concept of geometric transformation requires the design of learning developed based on learning obstacle analysis, repersonalization, and recontextualization so as to produce hypotheses consisting of Hypothetical Learning Trajectory which contains various activities and predictions of student responses and anticipations and produces Student Worksheets. The results show that the didactic design provided can overcome student barriers. It can be seen from the effectiveness of anticipation given during learning that reaches 90% of the difficulties that arise based on predictions of response and anticipated didactic pedagogical.